Effect of Learning Orientation on Innovation: A Mediating Role of Knowledge Competence - Ni Made Wahyuni; I Gusti Ayu Ketut Giantari (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
The purpose of this research was to investigate the effect of learning orientation on innovation, and knowledge competence as a mediator between learning orientation and innovation. The research collected data from 70 managers of manufacturing SMEs in Bali Province responded to the research questionnaires, and then the data were analyzed by using structural equation modeling with the partial least square approach. The results of this research show a significant and direct effect of learning orientation on innovation, learning orientation on knowledge competence, and knowledge competence on innovation. Furthermore, the results of the research show an indirect influence between learning orientation and innovation, which is mediated by knowledge competence. The findings of this research empirically show that learning orientation has a positive effect on knowledge competence, and knowledge competence has an important mediating effect to be managed to explain the mechanism by which learning orientation encourages innovation. Based on the research result, therefore, it can be concluded that this research offers empirical evidence about the relationship of learning orientation, knowledge competence and innovation. This research makes a theoretical contribution to the clarification that high learning orientation levels can increase innovation capacity. An important finding of this research is the role of learning orientation to increase innovation through the mediation of knowledge competence.